Peran Asam Lemak Tak Jenuh dalam Meningkatkan Kesehatan Metabolik dan Reproduksi Ternak Sapi Perah: Literatur Review - Humairoh, Ati; Ramadhan, Firdaus; Sidik, Abdul Fathir; Ruslan, Muhammad; Fauzan, Ahmad; Nurrofingah, Ulfa; Nafisah, Ainun (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The transition period in dairy cows is a critical phase characterized by increased energy requirements with the onset of lactation, while feed intake is often insufficient to meet these demands, leading to negative energy balance (NEB) that adversely affects metabolic health and reproductive performance. Therefore, this literature review aims to evaluate the role of unsaturated fatty acid (UFA) supplementation, particularly polyunsaturated fatty acids (PUFA), in mitigating NEB and improving the physiological performance of dairy cows based on recent scientific findings published between 2016 and 2025. The results indicate that UFA supplementation, especially rumen-protected sources, contributes to improved energy balance, enhanced insulin sensitivity, improved oocyte and embryo quality, increased plasma progesterone concentrations, reduced systemic inflammation, and improved blood lipid profiles. In addition, UFA supplementation helps maintain milk yield while enhancing milk quality through increased levels of unsaturated fatty acids and conjugated linoleic acid (CLA). With appropriate formulation, dosage, and timing of supplementation, UFA represents an effective and sustainable nutritional strategy to improve metabolic health, energy efficiency, and reproductive performance in dairy cows